Phenology of some dipterocarps - Nguyen-The, N.; Sist, P. (1998)
Phenological observations have been carried out on all the dipterocarps (except the genera Vatica and Hopea) recorded on 20 ha of mixed lowland dipterocarp forest in the Berau district (Kalimantan Timur, Indonesia). More particularly, a fruiting peak was observed at the end of January 1995. Although fruiting trees were observed in all diameter classes from 10 cm dbh, it turned out that the proportion of fertile trees was maximum and stable only above 50 cm dbh, which could be considered as a limit of maturity for dipterocarps. Considering only the trees above 50 cm dbh, the proportion of fruiting individuals was 66%, which is defined as a "mast fruiting" in the literature. Nevertheles, this fertility varied between genera. The genus Dipterocarpus participated at 82.3% while the genus Shorea participated at 54.5%. Within one genus, differences between species were also observed